Occupational emergency medicine - Greenberg, Michael I.; Madsen, James M. (Chichester, West Sussex, UK : Wiley-Blackwell, 2011)
With a large proportion of emergency admissions due to occupational health problems, the effect this can have on your practice cannot be ignored. Owing to the shortage of occupational physicians and limited worker access to health care, the diagnosis and treatment of occupational diseases rely increasingly on the emergency physician. Apart from extra paperwork, owing to the extra legal and administrative regulations, a lack of knowledge of occupational medicine can risk a missed diagnosis. This burden of work means occupational disorders impact the whole of the emergency department. Michael Gre.
Potentially lethal occupational exposures / Christina Price and Dennis P. Price -- Occupational dermatology : issues for the emergency department / David Vearrier -- Occupational infections / Amy J. Behrman -- Occupational toxicology / John Curtis and David A. Haggerty -- Work-related trauma and injury / Mark Saks and Brad Rahaman -- Occupationally based disaster medicine / James M. Madsen -- Work-related ocular injuries / Joseph L. D'Orazio -- Occupational illness and injury in law enforcement personnel / Richard Tovar -- Occupational illness and injury in firefighters / Richard Tovar -- Occupational illness and injury in prehospital care personnel / Derek Isenberg and Carin Van Gelder -- Occupational pulmonary disease / Michael G. Holland -- Health hazards and emergency care for health care workers / Amy J. Behrman -- Occupational concerns for truckers and drivers / Natalie P. Hartenbaum -- Arts medicine : an overview for emergency physicians / Robert T. Sataloff and Mary J. Hawkshaw -- Occupational hearing loss : an overview for emergency physicians / Robert T. Sataloff, Mary J. Hawkshaw, and Joseph Sataloff -- Voice disorders : an overview for emergency physicians / Robert T. Sataloff and Mary J. Hawkshaw -- Unusual problems in occupational emergency medicine / Edward A. Ramoska and Guneesh Saluja.
Includes bibliographical references and index.
Print version record.
Keywords: Occupational diseases; Medical emergencies; Industrial toxicology; Toxicological emergencies; Medicine; HEALTH & FITNESS -- Work-Related Health; MEDICAL -- Occupational & Industrial Medicine; Industrial toxicology; Medical emergencies; Occupational diseases; Toxicological emergencies; Emergencies; Occupational Diseases -- therapy; Accidents, Occupational; Emergency Service, Hospital; Occupational Exposure -- adverse effects; Electronic books